Biological aspects of Leucothyreus ambrosius Blanchard (Coleoptera, Melolonthidae, Rutelinae) - Gomes,Elias Soares (2014)
Biological aspects of Leucothyreus ambrosius Blanchard (Coleoptera, Melolonthidae, Rutelinae). Coleopterans of the family Melolonthidae comprise a large group of species that feed on different food sources, including plant roots, stems, and leaves, in addition to plant materials at different decomposition stages. Several species are found in the genus Leucothyreus, occurring in different regions of Brazil, including the various biomes in the country. Information on the biology of species of the genus Leucothyreus is scarce, therefore, we conducted studies on the biological aspects of Leucothyreus ambrosius Blanchard, 1850. The period of adult occurrence was determined with a light trap installed between a cropped and pasture area in the municipality of Aquidauana, Mato Grosso do Sul State, Brazil. Adults collected in the field were used to form insect pairs and the studies were initiated in the entomology laboratory as the adults began ovipositing. Adults were observed flying in the field from October to December. Eggs were obtained as pairs were formed and a colony was established, the embryonic period lasting 14.6 days on average. The larval period in the 1st instar lasted 21.6 days, in the 2nd instar 19.6 days, and in the 3rd instar, 85.6 days. The head capsule width was 1.48 mm in the 1st instar, 2.44 mm in the 2nd, and 3.83 mm in 3rd larval instar. The pupal stage had an average duration of 35.5 days. The egg to adult period lasted 173.3 days. Morphometric information for the larval and adult stages is presented in this study.